LOYALITAS SANTRI (TEAMWORK) TERHADAP KEPEMIMPINAN KIAI DALAM MANAJEMEN PESANTREN - Kurniawan, Asep (Pascasarjana IAIN Kudus, 2013)
The loyal teamworks are a key of successful management of Islamic boarding school. That loyalty does not happen accidentally, butcaused by a clear vision and the goal congruence of the insiders.Teamworks require individual commitment by maintaininguniqueness of the individual and respect for differences. Consideringteamwork is an integral part of the management of Islamic boardingschool, so it is found that the loyalty to the kiai leadership is verystrong. Teamworks Islamic boarding school loyalty arises from kiaileadership who uses the model-collegial partners, the exemplaryand spiritual leadership. The essence of leadership is a test, amandate from God and man, and influencing teamworks, so a leadermust show an exemplary, inspiration, actuating, and humanizing.The targets of leadership are to build affection, to spread virtue,and to channel the Mercy of God.